A STUDY TO EXPLORE THE SMARTPHONE DEPENDENCE AND ITS EFFECTS ON HEALTH AMONG COLLEGE STUDENTS IN SELECTED COLLEGES AT PUDUCHERRY U.T. - Chozharajan, J (LIFE: International Journal of Health and Life-Sciences, 2018)
A study to explore the Smartphone dependence and its effects on health among college students in selected colleges at Puducherry U.T.The objectives of the study was to identify the Smartphone dependence among selected college students, to evaluate effects of Smartphone usage and its effects on health among college students, to compare the level of Smartphone dependence and its effects on health with selected colleges and to associate the Smartphone dependence with selected socio demographic variables. The research approach selected for the study was quantitative research approach and descriptive survey design. The study was conducted at selected colleges at Puducherry U.T. 560 samples were selected bases on purposive sampling technique. The researcher used structured questionnaire for data collection. The outcome of the study was evaluated by using descriptive and inferential statistics. The findings of the study revealed that out of the total samples the medical, engineering and dental students are more dependent on Smartphone (35.63%) but the less dependent of Smartphone are nursing students (30.24%) but the paramedical, arts and laws are in between medical students and nursing students(31.49%).and medical, engineering and dental students are more affected on health by usage of Smartphone (15.59%) but the less affected on health are nursing students (13.75%) but the paramedical, arts and laws are in between medical students and nursing students(14.09%). There will be statistically significant difference between Smartphone dependence and its effects on health with selected colleges at p<0.05 level. There was a statistically significant association with level of dependency on Smartphone at p<0.001 level. Educational qualification, Smartphone use per day (hrs), had shown statistically significant association with level of dependency on Smartphone at p<0.001 level. Promotion of the IEC, creation of awareness among the college students can effectively control the Smartphone dependence.